2015
DOI: 10.1016/j.jor.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and haematological predictors of acute hematogenous Methicillin Resistant Staphylococcus aureus (MRSA) osteomyelitis & septic arthritis

Abstract: Results: Of 81 patients enrolled in the study, 61 were culture positive (22% MRSA). Statistically significant difference was found only in CRP (P < 0.001). ROC curve analysis shows that CRP levels of >13.9 mg/L, MRSA bone and joint infection could be predicted with 92.9% sensitivity and 79.1% specificity (AUC ¼ 89.1). Conclusion:Estimation of serum CRP levels at the time of presentation can aid in distinguishing MRSA osteomyelitis from non MRSA one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Infection is one of the most common causes for emergency admissions in orthopaedic surgery along with trauma. S. aureus was the most commonly cultured organism in this study and is consistent with reports from all over the world (Table ). Only one adult in the series had Haemophilus influenzae infection.…”
Section: Discussionsupporting
confidence: 91%
“…Infection is one of the most common causes for emergency admissions in orthopaedic surgery along with trauma. S. aureus was the most commonly cultured organism in this study and is consistent with reports from all over the world (Table ). Only one adult in the series had Haemophilus influenzae infection.…”
Section: Discussionsupporting
confidence: 91%
“…A study from France, which spanned three decades between the years of 1979‐2008, showed minimal changes in the rates and nature of causative organisms of SA. In contrast, studies from west Texas, California and other countries identified an increase in the rates of methicillin resistant Staphylococcus aureus (MRSA) SA 1,3,4,11‐16 …”
Section: Introductionmentioning
confidence: 97%
“…However, the negative rate of bacterial culture results ranged from 30% to 50% [20,21]. Even in cases with positive culture results, the pathogenic bacteria may take days to culture and isolate, often delaying the use of the most sensitive antibiotics [22]. Early bacteriological culture of pus collected by local puncture to identify pathogenic bacteria and conduct sensitivity testing may effectively improve the cure rate of the disease and reduce its complications.…”
Section: Discussionmentioning
confidence: 99%